Hungarian Monitoring, 1 July 1989 . [Magyar rádiófigyelő], 1989. július 1 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Transcripts of Hungarian national radio programs produced by the Hungarian Monitoring Unit of Radio Free Europe/Radio Liberty. A magyar országos rádióadók műsorainak a Szabad Európa Rádió/Szabadság Rádió Magyar Monitoring Osztálya által készített átiratai. International Politics: - Complications over Polish presidential candidate - Many researchers criticize Soviet intervention in Hungary in 1956 at roundtable discussion organized by Novoye Vremya - More skirmishes between Georgians and Azerbaijanis Domestic Affairs: - Mátyás Szűrös at 12th Hungarian peace conference - Debate over conciliation talks' power to restrict parliament - Party of the street, the Hungarian October Party unveils its flag: interview with three of its representatives - Deputy chief prosecutor to submit legal appeal on June 6 against decision taken in the case of Imre Nagy and colleagues - Confession of Veszprém County leader János Papp: I was a faithful follower of Kádár - Political scientist György Fischer on the wars raging in the Social Democratic Party - Gabčíkovo-Nagymaros dam commissioner on the Czechoslovak standpoint Economy: - Mátyás Szűrös confirms that the predominant role of state ownership must be terminated in Hungary Külpolitika: - A lengyelországi elnökválasztási jelölt körüli bonyodalmak - A Novoje Vremja által rendezett kerekasztal beszélgetésen több kutató is elítélte az 1956-os magyarországi szovjet bevonulást - Ismét összetűzések voltak grúzok és azerbajdzsánok között Belpolitika: - Szűrös Mátyás a 12-ik magyar békekonferencián - Vita az egyeztető tárgyalások parlamentet korlátozó hatásáról - Zászlót bontott az utca pártja, a Magyar Október Pártja. Interjú a párt három képviselőjével - Július 6-án nyújtja be törvényességi óvását a legfőbb ügyész nevében helyettese, Nagy Imre és társai ügyében - Papp János, Veszprém megye vezetőjének vallomása: Kádár hithű követője voltam - A Szociáldemokrata Pártban dúló harcokról a politológus Fischer György - A bős-nagymarosi beruházás biztosa a csehszlovák álláspontról Gazdaság: - Szűrös Mátyás megerősítette, hogy Magyarországon meg kell szüntetni az állami tulajdon uralkodó szerepét